2004
DOI: 10.1021/ja0474547
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient, One-Step Macrocyclizations Assisted by the Folding and Preorganization of Precursor Oligomers

Abstract: Highly efficient, one-step macrocyclizations leading to the formation of macrocyclic hexa(aramides) in high yields (69-82%) are described. The one-step macrocyclizations were facilitated by the preorganization or folding of the backbones of uncyclized precursors in the course of macrocyclization. The preorganization of backbones was achieved by the presence of localized three-centered hydrogen bonds that were adopted in the design of a class of closely related, backbone-rigidified foldamers. The macrocyclizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 155 publications
(97 citation statements)
references
References 30 publications
1
93
0
3
Order By: Relevance
“…As a result, a highly efficient macrocyclization is achieved. 259 Studies at different temperatures showed that the 6-mer macrocycle 219 predominated when the macrocyclization reaction was carried out at low temperatures, and the formation of the 8-mer macrocycle increases at higher temperatures, which was assigned to the augmented flexibility of the folded oligomeric species (Figure 63). 260 The same group also studied the role of the geometry of the precursors by performing competing kinetic experiments.…”
Section: Conformational Preorganizationmentioning
confidence: 99%
“…As a result, a highly efficient macrocyclization is achieved. 259 Studies at different temperatures showed that the 6-mer macrocycle 219 predominated when the macrocyclization reaction was carried out at low temperatures, and the formation of the 8-mer macrocycle increases at higher temperatures, which was assigned to the augmented flexibility of the folded oligomeric species (Figure 63). 260 The same group also studied the role of the geometry of the precursors by performing competing kinetic experiments.…”
Section: Conformational Preorganizationmentioning
confidence: 99%
“…The former has mainly been used because of the ease of synthesis, but usually suffers from low yields as a result of numerous cyclic and noncyclic side-products. [4,5] Recently, some elegant developments of this strategy were reported [6][7][8][9][10] which constitute a significant advance as far as suppression of side-reactions during cyclization is concerned. The building blocks required, however, have a higher structural complexity which unfortunately directly translates into greater effort in their synthesis.…”
Section: Comments On Strategymentioning
confidence: 99%
“…[47,48] In 2004, Gong and co-workers reported the one-step synthesis of macrocycles 35a-d in 69-82% yields from the corresponding diamine and diacyl chloride precursors. [49] When benzene-1,4-dicarboxylic acid precursors were introduced, the cavities of the macrocycles could be enlarged remarkably. [47] Li and Yuan et al also utilized a similar strategy to prepare a number of aromatic amide macrocycles from different diamines and diacyl chlorides, [50,51] while Huc and Jiang et al reported the synthesis of several aromatic amide macrocycles through the self-coupling of discrete quinoline amino acids.…”
Section: Promotion Of Covalent and Noncovalent Macrocyclizationmentioning
confidence: 99%